CONFLICTS OF THE MAIN CHARACTER IN RACHAEL LIPPINCOTT'S FIVE FEET APART - Adyaqsha; Tini Mogea; Delli Sabudu (Program Studi Pendidikan Bahasa Inggris, 2023)
The purpose of the research was to reveal the conflicts of the main character in Rachael Lippincott’s novel “Five Feet Apart”. The author uses a qualitative method to this research. This study can be classified as a library research because the data were collected through reading the novel and reading some books, dictionary, journals and internet which are related to the topic. The novel can be categorized as the primary source and the other sources can be categorized as secondary sources. In analyzing the data, the researcher used psychological approach because it is very close with human life, such as feeling, thoughts and desire. The result showed that there are 2 kinds of conflict that appear in this research, internal and external. Internal conflict about how Stella’s mind thinks about her genetic rare disease, while the external conflict discusses about how Stella Grant faces many people around her to struggle against cystic fibrosis (her disease).